Narrativity and the Patterning of Experience: Reading Hemingway as Part of the Popular Culture - Gordić Petković, Vladislava S. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The narrative form requires a capacity of structuring and patterning both the language and the experience: its objective is the attribution of meaning and articulation of experience. Reading is a process which produces its own fictional truths by prioritizing a coherent historical focus rather than the puzzling elements of the identity which cannot be observed, analyzed or reconstructed. According to Teresa de Lauretis, “the history proper, in the modern definition, achieves both narrativity and historicality by filling in the gaps left in the annals and by endowing events with a plot structure and an order of meaning” (de Lauretis, 1984, pp. 127-8). In the mythical-textual mechanics, the protagonist is predetermined to be of male gender, whereas his chief interest and main obstacle must be female (de Lauretis, 1984, p. 119). This practice turns out to be universal, and we can observe it in many fields: in arts and in popular culture alike, in epics, stories, novels and non-fiction as much as in TV shows which put male figures at the centre. The mythical subject is typically male, “he is the active principle of culture, the establisher of distinction, the creator of differences”, unlike the female who is not “susceptible to transformation, to life or death” but rather a mere “element of plot-space, a topos, a resistance, a matrix and matter” (de Lauretis, 1984, p. 119). The paper will focus on some narrative strategies and cultural practices Hemingway’s fiction is working with.